2016
DOI: 10.1021/acschemneuro.6b00313
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on 16-Arylideno Steroids as a New Class of Neuroprotective Agents for the Treatment of Alzheimer’s and Parkinson’s Diseases

Abstract: Neuroinflammatory mechanisms mediated by activated glial and cytokines (TNF-α, IL-1β) might contribute to neuronal degeneration leading to Alzheimer's (AD) and Parkinson's disease (PD). Lipopolysaccharide (LPS) is an inflammogen derived from the cell wall of Gram-negative bacteria, which promotes neuroinflammation and subsequent neurodegeneration. Dehydroepiandrosterone (DHEA) and testosterone have been reported as neuroprotective steroids useful for the treatment of various neurodegenerative disorders. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 44 publications
(95 reference statements)
1
36
0
Order By: Relevance
“…Benzylidene derivatives obtained by the Claisen–Schmidt condensation of steroidal ketones may serve as starting materials for the synthesis of compounds of pharmacological importance or may show favourable biological activity themselves . The 16‐arylidene group was found to be a good pharmacophore for cytotoxic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Benzylidene derivatives obtained by the Claisen–Schmidt condensation of steroidal ketones may serve as starting materials for the synthesis of compounds of pharmacological importance or may show favourable biological activity themselves . The 16‐arylidene group was found to be a good pharmacophore for cytotoxic activity.…”
Section: Introductionmentioning
confidence: 99%
“…In another area of therapeutic interest, two recent studies involving biomedical-steroid function, promise to lead to interesting structure function studies. It was shown that 16,17-pyrazoline substituted heterosteroids [21] and 16-arylideno steroids [22] both represent a new class of neuroprotective agents for the treatment of Alzheimer's and Parkinson's diseases. In particular it was shown that the introduction of a pyrazoline ring at the 16,17 position of the steroid skeleton resulted in improvement of neuroprotective effects.…”
Section: Conclusion and Proposed Future Studiesmentioning
confidence: 99%
“…Recently Singh and Bansal reported the neuroprotective effects of 16 ‐ pyridylidene steroids and their 4‐aza analogues in LPS (lipopolysaccharides)‐treated animal models . It was observed that the 16 ‐ arylidene steroidal derivatives significantly improve LPS‐induced learning, memory, and movement deficits in animal models.…”
Section: Neuroprotective Steroidsmentioning
confidence: 99%
“…Synthetic modifica- Recently Singh and Bansal reported the neuroprotective effects of 16-pyridylidene steroids and their 4-aza analogues in LPS (lipopolysaccharides)-treated animal models. 190 It was observed that the 16-arylidene steroidal derivatives significantly improve LPS-induced learning, memory, and movement deficits in animal models. In addition, the results of biochemical estimations of brain serum of treated animals have shown the suppression of oxidative and nitrosative stress, AChE activity, and reduction in TNF-levels, which were induced through LPS-mediated neuroinflammatory mechanisms.…”
Section: Androstane Derivativesmentioning
confidence: 99%
See 1 more Smart Citation